Post-traumatic stress disorder and its relation to irrational thoughts University studentOn a sample of Al Baath -- Diagnostic study - Batikh, Lina; Hazim , Kinan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Research aimed to reveal the relationship between PTSD and irrational thoughts in a sample of Ba'ath University students, Consisted the research sample of (509) male and female students of the first year of the Faculty of Education - Baath University and from difference specialties, Use the two researchers a list of traumatic experiences, and test of PTSD, prepared by Hanna, 2016 and test irrational beliefs prepared by Suleiman alryhany the two test are reliable and had a good degree of validity and reliability The results showed 1-. Post-traumatic stress disorder prevalence among the study sample (48,85%) 2- the prevalence of irrational ideas among the study sample (37.5%).3 - There is statistical significance correlational relationships between PTSD and irrational thoughts in the study sample. 4. There are statistically significant differences between students who saw traumatic experience and students who experienced traumatic experience in PTSD and the difference for students who saw the traumatic experience. 5- There are no statistical significance differences between students who saw shocking experience and students who have experienced traumatic experience in irrational ideas.